POLÍTICA E ESTÉTICA NA COMUNICAÇÃO POPULAR: Um estudo sobre os vídeos documentários Grito dos Excluídos da Associação Rede Rua - Almeida, Argemiro Ferreira de (2011)
This dissertation studies the documentary videos Grito dos Excluídos, produced from 1995 to 2009 by Associação Rede Rua. The purpose is to find, in popular communication, political and aesthetic dimensions as constants of great significance in the composition of a communicative praxis, which is either developed in the popular milieu or addressed to it. Starting with the context of production of the documentaries we reflect on this singular communicative praxis developed by Rede Rua. We also attempt to understand the way in which this praxis produces political and aesthetic reflexes on the materialized work of the video and on its specific manner of recreating reality. The study is based on bibliographical and documental research as well as the participant research and the study of parts of the documentaries. We concluded that they emphasize the denunciative, claiming and annunciatory character of a group of organizations, entities and popular social movements which try to influence Brazilian society positively and whose aim is to overcome the excluding logic of reality that limits and subjects peoples‟ rights to the power of money. Although the videos show political positions, they cannot be understood, in its material form, as political actors . Nevertheless, the present work emphasizes that the aesthetics of the documentaries is manifested as undisjoinable from its political character, since it clearly shows the commitment of its producers to the transformation of an excluding daily reality.